Uneven distribution of nanoparticles in immiscible fluids: Morphology development in polymer blends - Fenouillot, F.; Cassagnau, P.; Majesté, J.-C. (Polymer (Guilford), 2009)
The present review aims at summarizing the current knowledge on how solid nanoparticles organize in polymer blends. First, the behavior of low viscosity fluid emulsions containing solid colloidal particles is briefly presented. By contrast with polymer blends, they have been the subject of intensive studies for a long time, with both applicative and comprehensive objectives. High viscosity fluid emulsions like polymer blends loaded with nanofillers have received less attention until the recent enthusiasm about nanotechnology and more specifically polymer nanocomposites. Some similarities and differences between both types of emulsions are highlighted. The solid particles are well known to distribute unevenly in those types of complex fluids and the factors that determine their distribution in polymer blends are discussed. A particular emphasis is given on the competition between thermodynamic wetting of the solid by the polymeric phases and kinetic control of the filler localization directly linked to the rate of the mixing process. This aspect is believed to be a specificity of filled polymer blends and is known to have a drastic and sometimes predominant effect on particle localization. It explains that finely tuned morphologies can be obtained where the particles do not occupy their equilibrium position. [Display omitted]